2002
DOI: 10.1159/000057955
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Vitamin D- Dependent Hereditary Rickets

Abstract: Vitamin D exerts a wide variety of biological actions. The active form of vitamin D, 1α,25(OH)2D3, is biosynthesized from cholesterol. The final, critical step in this biosynthesis is conversion from 25-hydroxyvitamin D3 to 1α,25(OH)2D3 by the enzyme 25-hydroxyvitamin D3 1α-hydroxylase(CYP27B1)[1α(OH)ase]. 1α,25(OH)2D3 transcriptionally controls the expression of a particular set of target genes mediated through nuclear vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
(45 reference statements)
1
26
0
5
Order By: Relevance
“…Vitamin D receptor (VDR) (Ϫ/Ϫ) mice were generated by gene targeting as previously described (10,36). VDR genotypes were confirmed by analyzing the DNA obtained from each mouse ϳ3 wk after birth.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D receptor (VDR) (Ϫ/Ϫ) mice were generated by gene targeting as previously described (10,36). VDR genotypes were confirmed by analyzing the DNA obtained from each mouse ϳ3 wk after birth.…”
Section: Methodsmentioning
confidence: 99%
“…Defects in vitamin D activation and action cause different forms of vitamin D-dependent rickets whereas impaired degradation of 1,25-(OH) 2 D 3 underlies idiopathic infantile hypercalcemia (IIH). 1,2 IIH (OMIM #143880) was first described in the 1950s after an epidemic occurrence of unexplained hypercalcemia in infants receiving increased amounts of vitamin D via fortified milk products for the prevention of rickets. 3,4 Although a link to exogenous vitamin D was recognized early, the pathophysiology remained unknown until the recent identification of inactivating mutations in CYP24A1.…”
mentioning
confidence: 99%
“…An increased prevalence of diabetes has been observed in vitamin D-deficient individuals (4) , and our previous study has shown that vitamin D 3 treatment restores blood glucose homeostasis in streptozotocin (STZ)-induced diabetic rats (5) . Binding of vitamin D 3 promotes the vitamin D receptor (VDR) to form a heterodimer with the retinoid X receptor and transactivates vitamin D-responsive elements present in target genes (6) . VDR mRNA and protein have previously been detected and studied in several rat tissues including liver (7,8) .…”
mentioning
confidence: 99%